Motor response to apomorphine and levodopa in asymmetric Parkinson's disease. Issue 5 (May 1994) - Rodriguez, M; Lera, G; Vaamonde, J; Luquin, M R; Obeso, J A
Abstract : The motor responses of 14 patients with Parkinson's disease (six previously untreated and eight chronically receiving levodopa) with pronounced asymmetry in the severity of motor signs between the left and right sides of the body were studied. The effects of a short (60 minutes) and a long (16-22 hours) intravenous levodopa infusion as well as of subcutaneous apomorphine (1-6 mg bolus) were assessed. Four different tapping tests were used to measure motor function. For all pharmacological tests, the more affected side showed a shorter response duration, increased latency, and greater response magnitude than the less affected side. These differences were more pronounced in those patients receiving chronic levodopa treatment. As apomorphine is not dependent on dopamine storage capacity, these findings suggest that postsynaptic mechanisms play an important part in the origin of motor fluctuations in Parkinson's disease.